Research Landscape of Filipino Mathematicians a Co-authorship Network Analysis - Yu, Paul K. (Philippine Journal of Science, 2024)
Research collaboration presents solutions to various problems that independent researchers might encounter; however, establishing collaboration also poses challenges for most of these researchers. In this study, we created a co-authorship network map of Filipino mathematicians using Elsevier's Scopus database and identified the top five institutions with the largest number of Filipino mathematicians, each with at least one publication in Scopus. We found that among the top three institutions, collaborations rarely occur, with less than 1% distinct inter-institutional collaborations. Various network analysis metrics were performed on the map to establish a baseline for future co-authorship network research. Mathematicians were ranked using both the PageRank algorithm and betweenness centrality to highlight important and bridging figures, respectively. We found that while Canoy SR of Mindanao State University-Iligan Institute of Technology (k = 61), Corcino RB of Cebu Normal University (k = 39), and Mendoza ER of De La Salle University (k = 27) have notable contributions, the University of the Philippines Diliman (UPD) stands out with the most mathematicians having k ≥ 10, where k is the measure of degree centrality. The Leiden community detection algorithm was employed to cluster the network map, revealing 183 distinct clusters – indicating the number of cliques, which are small, exclusive research groups. This highlights the need to strengthen collaborative efforts among Philippine institutions. Interestingly, we found that UPD encompasses a broad range of mathematics research, indicating the potential to serve as a bridge connecting different subject areas. By illustrating the research landscape, this study sheds light on Filipino mathematicians' research, contributing to the enhancement of mathematics research productivity and collaboration in the country.